Microbial Degradation and Valorization of Plastic Wastes - Ru, Jiakang; Huo, Yixin; Yang, Yu (Frontiers in Microbiology, 2020)
Growing accumulation of plastic wastes has become a severe environmental and social issue. It is urgent to develop innovative approaches for disposal of plastic wastes. Recently, reports on biodegradation of synthetic plastics by microorganisms or enzymes spring up, which arouses our great enthusiasms to develop the biological treatment technology for plastic wastes. In this review, we comprehensively summarize the microorganisms and enzymes that have been reported to be able to degrade a variety of generally used synthetic plastics such as polyethylene (PE), polystyrene (PS), polypropylene (PP), polyvinyl chloride (PVC), polyurethane (PUR) and polyethylene terephthalate (PET). In addition, we highlight the microbial metabolic pathways for plastic oligomers and monomers such as styrene, terephthalic acid (TPA) and ethylene glycol (EG), and the current attempts towards utilization of such oligomers and monomers as feedstocks for microbial production of chemicals with high value. Taken together, these findings will contribute to build a conception of bio-upcycling plastic wastes by connecting the biodegradation of plastic wastes and biosynthesis of valuable chemicals in microorganisms. Last but not least, we discuss the challenges toward microbial degradation and valorization of plastic wastes.